2023
DOI: 10.1021/acsapm.3c00718
|View full text |Cite
|
Sign up to set email alerts
|

Polydimethylsiloxane Composite Sponge Decorated with Graphene/Carbon Nanotube via Polydopamine for Multifunctional Applications

Abstract: Recently, polydimethylsiloxane (PDMS)-based porous materials have been regarded as ideal candidates in various applications. We created a PDMS composite sponge decorated with reduced graphene oxide (rGO)/carbon nanotube (CNT) fillers via polydopamine (PDA). Specifically, a manufactured PDMS sponge was prepared by a sacrificial template approach and then PDA was decorated on a network of PDMS sponges by dopamine selfpolymerization. PDA tightly and firmly attached to the PDMS sponge skeleton, which makes the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…In addition, the gauge factor of the sensor was found to be 2.13. 116 Utilizing in situ transmission electron microscopy observation techniques, it is possible to manipulate a graphene layer at the atomic scale, achieving nanoscale sliding. Based on this technique a pressure sensor was fabricated, which demonstrated a high gauge factor of 4303 at maximum strain of 93.3%, low hysteresis, and high stability.…”
Section: In Situ Structural Health Monitoringmentioning
confidence: 99%
“…In addition, the gauge factor of the sensor was found to be 2.13. 116 Utilizing in situ transmission electron microscopy observation techniques, it is possible to manipulate a graphene layer at the atomic scale, achieving nanoscale sliding. Based on this technique a pressure sensor was fabricated, which demonstrated a high gauge factor of 4303 at maximum strain of 93.3%, low hysteresis, and high stability.…”
Section: In Situ Structural Health Monitoringmentioning
confidence: 99%
“…The single function of separation membrane cannot meet their requirements of practical wastewater purification. Thus, a membrane that can treat these contaminations simultaneously is still urgent needed 23,24 . Photocatalytic separation membranes, 25,26 self‐cleaning membranes, 27–30 and smart response membranes 31–33 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to matrix materials with high viscosity, micro- and nanomaterials capable of constructing rough structures are also required for the preparation of superhydrophobic coatings. In recent years, many studies have shown that carbon nanotubes (CNTs) are not only excellent materials for constructing hydrophobic surfaces but also have good photothermal conversion effects. Jiang et al developed a photothermal superhydrophobic coating using CNTs and silicon carbide. The contact angle test shows that the contact angle of water droplets on the surface of the coating is up to 161° and the rolling angle is less than 2°.…”
Section: Introductionmentioning
confidence: 99%